2020
DOI: 10.1167/iovs.61.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Interrogation in Cell Fate Decision of Cultured Human Corneal Endothelial Cells

Abstract: Aiming to clarify the metabolic interrogation in cell fate decision of cultured human corneal endothelial cells (cHCECs). METHODS. To analyze the metabolites in the culture supernatants (CS), 34 metabolome measurements were carried out for mature differentiated and a variety of cHCECs with cell state transition through a facility service. Integrated proteomics research for cell lysates by liquid chromatography−tandem mass spectrometry (LC-MS/MS) was performed for 3 aliquots of each high-quality or low-quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 41 publications
(69 reference statements)
6
50
0
Order By: Relevance
“…In a recent study, 15 our findings confirmed that the metabolic rewiring in the mature cHCECs provides essential cues underlying the dynamics of cell-fate modulation; however, and to the best of our knowledge, there have been no published reports with regard to a link between the metabolic rewiring of cHCECs and pHi homeostasis. The polarized expression of ion channels and SLC family transporters on two types of cHCECs may possibly indicate that the mature- and CST cHCECs can be distinguishable by their pHi.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…In a recent study, 15 our findings confirmed that the metabolic rewiring in the mature cHCECs provides essential cues underlying the dynamics of cell-fate modulation; however, and to the best of our knowledge, there have been no published reports with regard to a link between the metabolic rewiring of cHCECs and pHi homeostasis. The polarized expression of ion channels and SLC family transporters on two types of cHCECs may possibly indicate that the mature- and CST cHCECs can be distinguishable by their pHi.…”
Section: Resultssupporting
confidence: 79%
“…CE is one of the most metabolically active tissues in the human body. 14 In our recent study, 15 our findings revealed that the metabolic rewiring in mature differentiated cHCECs provides essential cues underlying the dynamics of cell fate modulation. In the previous preliminary studies, both Wang et al 16 and our group 4 found that metabolomic profiling segregated immature from mature differentiated cHCECs.…”
mentioning
confidence: 65%
See 3 more Smart Citations